The presa and the mother: social representations in the prison universe - Silvério, Raissa Lemos; Santos Filho, José dos Reis (Laboratório Editorial Faculdade de Ciências e Letras, 2017)
The article seeks to problematize the exercise of motherhood in prison the brazilian from the contradiction of the social representations that surround these women – the prey and the mother. From a literature review we present the construction of the representation of the mother in contemporary society, the vision of crime female while a breach of the standards of the genre, and, finally, the clash between the roles of criminal and a mother who are on poles diametrically opposite, grounded in the denial of identity in addition to the district of the person transgressive.